Effect of Forming Process on the Deformational Behaviour of Steel Pipes - Tanbakuei Kashani, Majid (Université d'Ottawa / University of Ottawa, 2017)
Buried pipeline networks play a vital role in the transportation of oil and natural gas from centers of production to centers of consumption. A common manufacturing technique for such pipes is the UOE process, where a flat steel plate is first formed into a U shape, then into an O shape, welded at the seam, and mechanically expanded before being shipped on site. The UOE forming process deforms the pipe material plastically and induces residual strains in the pipe. Such pipes are commonly buried on side and then are pressurized under the high head of the fluids they convey which induce hoop stresses as high as 80% of the pipe yield strength. When buried pipelines cross the regions of discontinuous permafrost, they undergo differential frost heaving, inducing significant bending deformations, which potentially induce local buckling in the pipe wall. To control local buckling, design standards impose threshold limits on buckling strains. Such threshold values are primarily based on costly full-scale experimental results. Past nonlinear finite element analysis attempts aiming at determining the threshold buckling strains have neglected the presence of residual stresses induced by the UOE forming and were thus found to grossly overestimate the buckling strains compared to those based experiments. Within the above context, the present study focuses on developing a numerical technique to predict the residual stresses induced during UOE forming, and incorporating the induced residual stresses in 3D nonlinear FEA modeling to more reliably predict buckling strain limits. Comparisons with conventional analysis techniques that omit residual stresses reveal the importance of incorporating residual stresses induced in forming when quantifying buckling strains.